The Influence of Food Reviews on Purchasing Decisions with Hedonic Style As a Moderating Variable: Penelitian - Otje Herman Wibowo; Mahmuddin; Rini Hadiyati; Sriwanti Belani; Ni Luh Ketut Ayu Sudha Sucandrawati (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This research is a quantitative study with an explanatory approach. The data used in this study is primary data obtained by the researcher from 335 J.CO Donuts customers spread throughout Indonesia. The data obtained by the researcher was analyzed using the smart PLS 4.0 analysis tool. The result in this article show that the first row of the table above, it shows the P-Values ​​are positive and below the 0.05 significance level, namely 0.006. These results are in line with the research. These results indicate that Food Reviewers can improve product quality, increase brand trust, increase sales quantity, and increase Purchase Decision numbers. In the next row, the results shown are three hundred and sixty degrees inverse, namely the Hedonic Style variable cannot moderate the influence of the Food Reviewer variable on the Purchase Decision variable because the P-Values ​​value is not below the 0.05 significance value, namely 0.068. This result is due to J.CO donut consumers purchasing based on product quality and brand trust, rather than hedonistic tendencies. Therefore, it can be concluded that the first hypothesis in this study is accepted, while the second hypothesis in this article is rejected.